MCM : La Storia delle Cose ; La Rivista delle Arti Minori. (Firenze.)
The magazine "MCM - La Storia delle Cose" has been dealing with art and culture and the artistic, environmental and craft heritage of Italy and Europe, fostering a knowledge of the same all over the world. The magazine features articles in dual language (Italian and English) and publishes four issues per year: March, June, September and December.(www.mcm.storiadellecose.it)
Http://www.mcm.storiadellecose.it
Italiaans
Tijdschriften